Analisis Pengaruh Penyertaan Modal Negara (PMN) Dan Pertumbuhan Aset Terhadap Kinerja Keuangan Pada Bumn Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Irfan Bintang Firdausi; Adam Zakaria; Muhammad Yusuf (LPPM Universitas Negeri Jakarta, 2024)
The purpose of this study was to empirically examine the effect of state equity participation and asset growth on financial performance in BUMN, with company size as a moderating variable. The sample selection in this study used the purposive sampling method. The data used in this study spanned five years, from 2018 to 2022. The number of BUMNs receiving PMN in the 2018–2022 period that fit the sample criteria was 11 companies multiplied by 5 years of observation, so the total research data was 55. Based on the results of the study, it can be seen that state capital participation has a positive and significant effect on financial performance, asset growth has a positive and significant effect on financial performance, company size does not moderate the effect of state capital participation on financial performance, and company size does not moderate the effect of asset growth on financial performance.